2021
DOI: 10.1001/jama.2020.22633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tidal Volume on Pulmonary Outcomes After Surgery

Abstract: Role of the Funder/Sponsor: The funders had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.Disclaimer: This article does not represent the views of the Department of Veterans Affairs or the US government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…Previous studies in critically ill patients have suggested that whilst lower inspiratory pressures are beneficial, higher respiratory rates may be harmful. 20 This led to an interest in how such opposing factors may interact. Mechanical power, a measure that aims to integrate static and dynamic parameters of ventilation, could be a more important variable in the relationship between ventilation and lung injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in critically ill patients have suggested that whilst lower inspiratory pressures are beneficial, higher respiratory rates may be harmful. 20 This led to an interest in how such opposing factors may interact. Mechanical power, a measure that aims to integrate static and dynamic parameters of ventilation, could be a more important variable in the relationship between ventilation and lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical power, a measure that aims to integrate static and dynamic parameters of ventilation, could be a more important variable in the relationship between ventilation and lung injury. 20 This is based on the rationale that VILI is not only a function of static parameters, such as strain from V T or stress from inspiratory pressures but also on the complex interplay between static and dynamic variables, including the rate of lung deformation (strain rate) and the cycling frequency, or respiratory rate. 14 20 Mechanical power has been suggested as an index of the overall energy applied to the lungs, which encompasses the impact of both driving pressure and respiratory rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ill patients 40 and a limited post hoc analysis of a randomized, controlled trial in the operating room. 16 The lack of effectiveness in randomized controlled trials of intraoperative mechanical ventilation interventions may be explained by the absence of a comprehensive focus on the multiple factors that contribute to ventilator-induced lung injury 9 -for example, increasing respiratory rate might offset effects of decreasing tidal volume, as observed in previous studies. 6 We found that only the dynamic elastic component was associated with greater risk of postoperative reintubation, but the static and dynamic resistive components were not.…”
Section: Mechanical Power and Postoperative Reintubationmentioning
confidence: 99%
“…7 While tidal volume was the only randomized variable in these studies, there was an associated increase in respiratory rate, potentially offsetting the beneficial effect of lowering tidal volume. 8,9 This illustrates the need for a unifying concept that integrates the effects of changes in multiple parameters when adjusting mechanical ventilation to reduce perioperative ventilator-induced lung injury.…”
mentioning
confidence: 99%